A Structural Equation Model For Adopting Additive Manufacturing in the Footwear Firms Supply Chains - Tekalign Lemma; Endalkachew Mosisa Gutema; Hirpa G. Lemu; Mahesh Gopal (Brazilian Journal of Operations & Production Management)
Goal: The objective of this research is to present a theoretical framework and explore how additive manufacturing (AM) techniques affect supply chain complexity (SCC) in the footwear sector.